Monocytes accumulate in the airways of children with fatal asthma. Issue 12 (16th October 2018) - Eguíluz‐Gracia, Ibon; Malmstrom, Kristiina; Dheyauldeen, Sinan Ahmed; Lohi, Jouko; Sajantila, Antti; Aaløkken, Ragnhild; Sundaram, Arvind Y. M.; Gilfillan, Gregor D.; Makela, Mika; Baekkevold, Espen S.; Jahnsen, Frode L.
Abstract: Background: Activated T helper type 2 (Th2) cells are believed to play a pivotal role in allergic airway inflammation, but which cells attract and activate Th2 cells locally have not been fully determined. Recently, it was shown in an experimental human model of allergic rhinitis (AR) that activated monocytes rapidly accumulate in the nasal mucosa after local allergen challenge, where they promote recruitment of Th2 cells and eosinophils. Objective: To investigate whether monocytes are recruited to the lungs in paediatric asthma. Methods: Tissue samples obtained from children and adolescents with fatal asthma attack (n = 12), age‐matched non‐atopic controls (n = 9) and allergen‐challenged AR patients (n = 8) were subjected to in situ immunostaining. Results: Monocytes, identified as CD68+S100A8/A9+ cells, were significantly increased in the lower airway mucosa and in the alveoli of fatal asthma patients compared with control individuals. Interestingly, cellular aggregates containing CD68+S100A8/A9+ monocytes obstructing the lumen of bronchioles were found in asthmatics (8 out of 12) but not in controls. Analysing tissue specimens from challenged AR patients, we confirmed that co‐staining with CD68 and S100A8/A9 was a valid method to identify recently recruited monocytes. We also showed that the vast majority of accumulating monocytes both in the lungs and in the nasal mucosa expressed matrix metalloproteinase 10, suggesting that this protein may be involved in their migration within the tissue. Conclusions and clinical relevance: Monocytes accumulated in the lungs of children and adolescents with fatal asthma attack. This finding strongly suggests that monocytes are directly involved in the immunopathology of asthma and that these pro‐inflammatory cells are potential targets for therapy.